Nasihat Berlakulah Adil dalam Haustafeln Kolose 4:1 - Albertus Lilik Kurniawan (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
This essay aims to make a biblical-theological analysis of Col. 4:1 in which Paul speaks about the responsibility of masters to treat their servants justly and fairly. This study uses a critical historical method while taking into account the sociological context of the biblical text (a sociological approach). Based on textual analysis, Col. 4:1 lies in a sequence of rules that govern the relationships between household members (Col 3:18-4:6), namely the relationship between husband and wife (3:18-19), parents and children (3:20-21), and the last is master and servant (3:22-4:1). Based on a sociological approach, this study finds that the Colossian Christian community had servants, and that’s why the treatment of servants became an unavoidable topic in good household management. The relationship between master and servant needs to be clarified from a Christian point of view. The instructions in Col. 4:1 are to say that the master is responsible for treating the servants justly and fairly, that is, doing what is right with his servant. Haustafeln also contains a Christological orientation because they aim to place the household under Christ, as all life must be subject to Christ.